A Study on the Influence of Mentoring Functions on Turnover Intention: MZ Generation in the Semiconductor Industry (aSSIST Business Review, 2025)
The semiconductor industry is a cornerstone of modern technological advancement and a critical driver of futureindustries. Due to its technical complexity and specialized nature, talent acquisition and retention are key determinantsof competitive advantage. However, the high turnover rates among the Millennial and Gen Z (MZ) workforce posesignificant challenges to organizational productivity and competitiveness. Existing studies predominantly focus on generalindustries, limiting their applicability to the unique characteristics of the semiconductor sector and the specific needs ofthe MZ generation.This study empirically analyzes the impact of mentoring functions on turnover intentions among MZ employees in thesemiconductor industry. Data were collected through a combination of surveys and in-depth interviews, and the primarymethods of analysis included correlation and regression analysis. The findings indicate that mentoring functions―careerdevelopment, psychosocial support, and role modeling―significantly influence turnover intentions.First, the career development function emerged as a critical factor in reducing turnover intentions. Guidance andtechnical support provided by mentors were found to enhance job satisfaction and organizational commitment, therebymitigating turnover intentions. However, in some cases, excessive career support inadvertently heightened turnoverintentions, as mentees sought opportunities elsewhere.Second, the psychosocial support function had the most substantial impact on reducing turnover intentions. Emotionalsupport and psychological stability offered by mentors fostered a sense of belonging and engagement within theorganization, effectively decreasing turnover intentions.Third, while the role modeling function showed positive effects in certain aspects, it was not consistently significantacross all variables. This suggests that mentors' values and behaviors may strengthen mentees' organizational commitmentunder specific conditions.In conclusion, mentoring programs play a pivotal role in reducing turnover rates and enhancing organizationalcommitment. Tailoring mentoring designs to the unique traits of the MZ workforce is essential for addressing their needsand fostering organizational adaptation and engagement. Organizations must prioritize a balanced approach to providingpsychological support and career development, while establishing trust-based relationships between mentors and mentees.This research provides strategic insights not only for the semiconductor industry but also for other technology-drivensectors aiming to optimize human resource management.
Keywords: Mentoring Program; Turnover Intention; MZ Generation Workforce; Semiconductor IndustryTalent Retention; Organizational Commitment & Psychological Support